Pengiriman Video secara Live Streaming Menggunakan Dynamic Adaptive Streaming over HTTP (DASH) - Hamid Azwar (Jurnal Elektro dan Mesin Terapan, 2020)
Bandwidth limitations and fluctuations in traffic on the network become obstacles in the process of sending video. At the time of the availability of small bandwidth and high network traffic, the process of sending video will take a long time due to the operation of slow video transmission or more commonly called buffering. This study evaluates sending live streaming video using the Dynamic Adaptive Streaming over HTTP (DASH) method on the LAN network. DASH is an adaptive streaming protocol that can present the video with video quality according to network capabilities on the client. This implementation is carried out using H.265 video compression and the streaming process is carried out on a LAN network with 20 live streaming clients. The results of this study obtained the value of video delivery throughput reaches 1.4 Mbps and the most significant delay value is 12.5 ms. The highest percentage of client requests for video quality for one client is 98%. As for the use of 20 clients, the demand for high-quality video is reduced to 46% which proves that DASH was successfully implemented live streaming. Keywords: Video, Live, Streaming, H.265, DASH